Entre a terra e o céu: habitação, verticalização e dinâmicas urbanas em São José do Rio Preto/SP - Lisbôa, Cristian Roberto Nazareth (Universidade Federal de São Carlos, 2024)
This study analyzes residential verticalization and urban space use in São José do Rio Preto, a medium-sized municipality in the state of São Paulo, which has experienced intense growth in its real estate sector and significant transformations in its urban landscape over the past two decades. Set within a context of housing financialization and hyper-commodification, the phenomenon of vertical urbanization, increasingly present in cities across various global contexts, has profoundly shaped the spatial configurations and socio-economic and cultural dynamics of urban spaces. The research investigates how this trend manifested in São José do Rio Preto between 2000 and 2022, promoting substantial changes in the urban landscape and impacting the lives of its residents. Through a mixed-methods approach, combining quantitative and qualitative analyses, the study evaluates the factors driving verticalization, exploring its causes, characteristics, and implications. The results reveal a significant increase in the number of apartments in the city, driven by factors such as changes in urban legislation, market pressures, and the activities of major urban developers, whose capital is frequently influenced by external markets. Spatial analysis, complemented by modeling techniques and the use of Geographic Information Systems (GIS), demonstrates an unequal distribution of verticalization across the Administrative Regions of São José do Rio Preto, with high-standard developments concentrated in the most valued areas; this growth pattern accentuates socio-economic and spatial disparities, relegating the lower-income population to peripheral areas. The study also broadens the analysis to the context of metropolitan regions in São Paulo, highlighting the polarization of verticalization in core cities, such as São José do Rio Preto and Ribeirão Preto, reinforcing their centrality as regional hubs of vertical development. The research further explores the growth dynamics of cities within the São José do Rio Preto Metropolitan Region, noting a localized expansion of verticalization in these areas, albeit with less impact than observed in the core city. This research contributes to the debate on the impact of verticalization on housing and urban development, considering the local setting and its connection to the regional context. It concludes that, although verticalization promotes urban densification, it also contributes to socio-spatial exclusion and the widening of inequalities, underscoring the need for more inclusive and sustainable public policies.
Between the ground and the sky: housing, verticalization, and urban dynamics in São José do Rio Preto/SP
Keywords: Verticalização; Urbanismo vertical; Mercado imobiliário residencial; São José do Rio Preto; Cidades de porte médio; Verticalization; Vertical urbanism; Residential real estate market; Medium-sized cities.; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::DEMOGRAFIA::DISTRIBUICAO ESPACIAL::DISTRIBUICAO ESPACIAL URBANA; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ESTUDOS DA HABITACAO